Un balcon sur l’Europe: Fin-de-siècle Art in Belgium. View from Russia - Klyushina, Elena V. (Actual Problems of Theory and History of Art, 2022)
In recent years, the turn-of-the-century art and culture in Belgium have attracted increasing attention from the international scientific community. Exhibitions devoted to Belgian symbolism and its individual representatives are being opened more and more often. The usual concepts and principles of museum exhibiting of fin-de-siècle art are being revised. There is a significant increase in publication activity, aimed at a comprehensive analysis of the artistic and aesthetic features of the genesis and development of the modern Belgian painting school. However, in Russian humanities only in the past few years, there has been a certain increase in research interest in the problems of Belgian art. The aim of the article is to demythologize the usual ideas about the peripheral and provincial nature of the Belgian art school, typical for Russian historiography. For this purpose, the author outlines the main development trends of the Fin-de-Siècle Belgian art, reveals original research approaches, which in recent years have proved their effectiveness, analyzes the few scientific works by Russian art historians that were devoted to the culture of this country, and proposes cutting-edge areas of study of the fine arts of Belgium, which could possibly serve as a basis for revising the approaches taken in modern Russian humanities to the study of the art of small European countries.